Melt-Electrospun Polyethylene Nanofiber Obtained from Polyethylene/Polyvinyl Butyral Blend Film - Mohammad Zakaria (Polymers, 2020)
We prepared low-density polyethylene (LDPE) nanofiber, a few hundred nanometers in diameter, using polyvinyl butyral (PVB) and a laser melt-electrospinning (M-ESP) device. We blended PVB with LDPE via an internal melt mixer, removed the PVB after M-ESP by ethanol treatment, and studied the influence of PVB on fiber diameter. A substantial diameter reduction with improved crystallinity of LDPE fiber was observed with increased PVB content in the blend. PVB inclusion also increased the polarity of the LDPE/PVB blend, resulting in better spinnability. The removal of PVB from LDPE/PVB blend fiber caused a massive drop in the LDPE fiber diameter, due to fiber splitting, particularly in PVB-rich samples. Fourier transform infrared (FTIR) spectroscopy of fibers confirmed that the prepared nanofiber was the same as pure LDPE fiber.